Research on the Application of Big Data and Artificial Intelligence in Search Engine - Hu, Hanzhe (International Journal of Computer Science and Information Technology, 2024)
With the development of the Internet, search engine as an important tool of information retrieval, more and more need to deal with large-scale, complex data. The combination of big data and artificial intelligence technology provides a new solution for search engine optimization. This paper mainly discusses the application of big data and artificial intelligence in search engine, including data collection and processing, data mining and pattern recognition, user behavior analysis, personalized recommendation algorithm, machine learning algorithm, deep learning algorithm, reinforcement learning algorithm and the intelligence of personalized recommendation system.